Tingkat Literasi Informasi Guru Sekolah Menengah Kejuruan Negeri (SMKN) Se-Kabupaten Lebong - Julia Salsabila; Nurhizrah Gistituati; Hanif Alkadri; Enceria Damanik (Jurnal Pendidikan, Sains Dan Teknologi, 2026)
Information literacy is an essential competency that teachers must possess to respond to rapid technological developments, the implementation of the Merdeka Curriculum, and the demands of 21st-century learning. However, the information literacy level of teachers, particularly those working in public vocational high schools (SMKN) in Lebong Regency, has not been empirically identified, making it necessary to provide an evidence-based description as a basis for teacher professional development. This study aimed to describe the information literacy level of teachers at public vocational high schools in Lebong Regency based on four indicators: identifying information needs, accessing information, evaluating information, and using information. This study employed a descriptive quantitative approach. The population consisted of 133 teachers from four public vocational high schools in Lebong Regency. The sample was determined using the Slovin formula with a 5% margin of error and distributed through proportional random sampling, resulting in 103 respondents. Data were collected using a 40-item Likert-scale questionnaire. The instrument met the validity requirements based on the Pearson Product Moment test and demonstrated high reliability with a Cronbach's Alpha coefficient of 0.974. Data were analyzed using descriptive statistics, including mean scores and the Respondent Achievement Level (TCR). The findings revealed that the overall information literacy level of teachers was in the moderate category, with a mean score of 3.87 and a TCR of 77.35%. The highest achievement was found in the information use indicator (80.36%), categorized as high, while the lowest achievement was in information access (74.26%), categorized as moderate. These findings indicate that although teachers have been able to utilize information effectively in teaching, their competencies in identifying information needs, accessing information, and evaluating information still require improvement through continuous professional development programs.